PERANCANGAN STRATEGIK DALAM PENTADBIRAN ISLAM: SUATU TINJAUAN PERBANDINGAN - Syed Ismail, Sharifah Hayaati (Jurnal Syariah, 2019)
Since the late nineteenth century, administration as a profession and academic study has been developed and evaluated based on quality, effectiveness and efficiency to enhance service delivery in pursuit of the public interest. The challenge in the era of twienty first century is globalization that changes the nature of world in which we live and work has confronting public administrators with range of problems and contraints. They can no longer be ethnocentric, inward looking, focused on the past and defensive in administration. Instead they nust be forward looking, globally oriented, innovative and ready to serve the community much more effective. And one way of putting this aim into reality is by planning work strategically. This is what this article is all about i.e. to introduce the concept of strategic planning for practical purpose as well as to discuss it in comparative mode with the idea of Islamic strategic planning. It is hoped that this article provides the reader with more comprehensive thought on strategic planning.